Group emotional intelligence and organizational health - Josheghan, Reza Ghaffari; Nazemi, Masome (International Journal of Education and Cognitive Sciences, 2022)
The aim of this study is to expose the relation between group emotional intelligence and the organizational health. The method of research is descriptive and correlative. The statistical community of this research includes the all primary and high school teachers in Esfarayen city at North Khorasan Province in Iran. According to Morgan table Selected 313 teachers who answered the questionnaires.  Research tools are two questionnaires including Emotional Intelligence Questionnaire (Bradberry & Greaves, 2005) and Organizational Health Inventory (Hoy et al., 1991). The results showed that the relationship between group emotional intelligence and organizational health is meaningful. Also there is relationship between self-awareness of groups with organizational health and also there is relationship between self-management of groups with organizational health. There is relationship between relationship-management and social awareness of groups with organizational health. There is a significant positive relationship between group emotional intelligence with organizational health.